Enhancing Reading Comprehension through Task Repetition Method: A Study at Vocational High School Makassar - Madjid, Masyita; Am, St. Asriati; Hamid, Radiah (UNIB Press, 2025)
Abstract This research aims to assess the effect of the Task Repetition Method on students' reading comprehension at Vocational High School 1 Makassar. Using a quasi-experimental research design, two classes, namely 36 students in the experimental and 36 students in control classes, were tested with pre-tests and post-tests. The data were collected by using reading test. The data were analysed using descriptive statistics from the SPSS 25.0 version. The result showed the students' reading comprehension enhanced more using the Task Repetition Method rather than the Task Rehearsal Method. The experimental class improved from a pretest score of 59.70 to 84.50 (41.54%) in literal comprehension, while the control class improved from 60.10 to 82.96 (38.00%). The control group increased from 58.40 to 79.00 (35.35%) in inferential comprehension, while the experimental group improved from 57.80 to 78.74 (36.28%). Higher proficiency in both comprehension aspects was attained by more students in the experimental class. The Task Repetition Method significantly improved students' comprehension and analysis of texts, according to the results of the t-test.